Plea Bargaining As A Reform of Criminal Procedural Law To Realize The Principle Of Swift, Simple, And Low-Cost Justice - Cavin George Ngilawane; Salvadoris Pieter; Mulyadi Alrianto Tajuddin (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2025)
The Indonesian judicial system faces persistent challenges, including chronic case backlogs and severe prison overcrowding, which undermine the constitutional principle of swift, simple, and low-cost justice. This study explores the necessity of integrating Plea Bargaining into Indonesian criminal procedural law through the